Determining psychological aspects of food behavior in children and adolescents with overweight or obesity - Oliveira Pereira, Fernando (Journal of Health Care, 2021)
Overweight and obesity are a conditions resulting from eating behaviors determined by the action of a multiplicity of factors inherent to the subject`s functionality as an integrated bio-psycho-social system. Research objective: Study of determinants of eating behavior in overweight or obese children and adolescents. Participants: 50 children and adolescents diagnosed with overweight/obesity, aged between 7 and 18 years, and another 50 with equivalent sociodemographic characteristics, which constitute the control group defined by weight and BMI criteria within standardized parameters. Methodological instruments: Clinical-psychological interview; sociodemographic questionnaire; Eating Behavior Questionnaire (EBQ). Results: Children and adolescents with overweight/obesity, compared to those in the control group, show significantly higher BMI and values of the "external food intake" dimension, with statistically significant differences. In the dimensions "food restriction" (less expressive) and "emotional food intake" (more expressive), the statistical differences are not significant, as to the number of inducers involved, but relate to the intensity or frequency of action. Conclusions: In overweight and obese children and adolescents, eating behavior was induced by sensory and cognitive-emotional determinants in conjunction with deficient concern and willpower in situations and circunstances. The latter required restriction of the quantity and types of food ingested, concerning eating habits and style. Eating behavior, in the perspective of psychological dependence, involves processes of emotional immersion, cognitive colonization, motivational submission and volitional subsidization.